Teacher’s Directive Expressions Analysis in English Teaching Classes - Haryanto Haryanto; Husni Mubarok (Lensa: Kajian Kebahasaan, Kesusastraan, dan Budaya, 2018)
This paper aimed at finding out the types of teacher‟s directive expressions at two schools and describing the realizations of directive expressions in English teaching. This research was designed as a qualitative and comparative study. The subjects of the research were English teachers at one Senior High School (first School) at Semarang city and one (second school) at Jepara city. The data of this research were gained through recording, observation and interview. The result showed that there were 11 illocutionary kinds found in the teacher‟s directive expressions at the first school, and 8 illocutionary types in teacher‟s directive expressions at the second school. The most illocutionary kind found in the conversation of teaching activity in both schools was question. The directive‟s expression in both schools used direct and indirect utterances. The teachers of first school more often used language instruction in the classroom because they applied varieties of directive expression. Meanwhile, the teachers at the first school used little directive expressions in English teaching because they did not apply varieties of directive‟s expressions. The implication in teaching learning English process is that teacher-centered and student-centered type of learning depends on the frequency of production of directive expressions. More directives the teacher expresses, more center the learning by the teacher. On the other hand, less directives the teacher expresses, less center the learning by the teacher.